Multicentric osteoblastoma-like: report of a rare case in the craniofacial region - Hugo Guilherme M. Jurema; Eduardo B. C. Bicca; Raul Jablonski Júnior
ABSTRACT The osteoblastoma-like tumor is a rare condition with limited information about its treatment in the current medical literature. The tumor histologically resembles osteoblastoma, although the imaging features are similar to those seen in primary vascular lesions. Due to the uncertainty in the biological behavior of this tumor and because it is an unusual diagnosis, treatment can be aggressive, such as amputation, en bloc resection, and/or chemotherapy. This work reports a rare case of a patient with multicentric osteoblastoma-like in the craniofacial region, treated aggressively with total resection of the lesions.